Identificación de la flora (árboles y arbustos), Existentes en el Campus CEYPSA, Cantón Latacunga - Chamorro Espinoza, Carlos Humberto (2015)
This research was based on the identification of flora (trees and bushes) of the campus CEYPSA, It has an extension of 81.19 hectares, as objective generate a taxonomic data base for the development of the field work proceeded in the path of three transects horizontally which allowed to quantify the current state of the trees and shrubs, it was applied a homogeneous methodology on the basis of a diagnosis and analysis on statistical graphics and pictures its physical components, ecological, taxonomic characteristics and uses; with inventory, there quantified were 1062 trees, 1100 shrubs, giving a total of 2162 species, in three areas of study distributed: study area bottom 831 species, study area average 704 species and the study area part high 627 species, Cypress (Cupressus macrocarpa), pine (Pinus radiata) species that stand out as tree species, in three areas of study, shrub species protruding acacia (Acacia melanoxylon), Basswood (Tilia platyphyllos), Tupirosa (L. camara mutabili), ornamental tobacco (Nicotiana glauca), broom (Retama shaerocarpa), chilca (Baccharis latifolia) in two study areas, in the study area top protrudes the Yagual (Broussonetia papyrifera), the composition tree and shrub were determined 49 species, 37 families which have adapted providing plant coverage and landscape beautification for environmental stewardship.